How does spatial planning work? Implementing instruments for managing settlement development in Germany and Switzerland - Kießling, Nadine; Pütz, Marco (Raumforschung und Raumordnung | Spatial Research and Planning, 2022)
In Germany and Switzerland, land use and urban sprawl there has been a central topic of public debate for several years. Cantonal structure plans in Switzerland as well as state and regional plans in Germany contain binding regulations for managing settlement development. Studies that examine the implementation of these regulations are lacking. This paper analyses the implementation of selected instruments of supra-local spatial planning for managing settlement development in Germany and Switzerland using the Policy Arrangement Approach. The case study covers the regions Oberland (Bavaria), Südlicher Oberrhein (Baden-Württemberg) and the cantons of Zurich and St. Gallen. The results show that actors implement spatial-planning instruments in situative negotiation processes in which they exploremargins and alternatives. Central to these processes is a regional specific overlapping of (i) interlinkings of formal and informal instruments, (ii) the interplay between local autonomy, supra-local control and superordinate context factors, and (iii) the overlapping of supra-local and regional discourses. The results show that the Policy Arrangement Approach helps to better understand how spatial planning works.